Realistic emulation of the operational environment for SatCom On-The-Move (SOTM) terminals - Alazab, Mostafa; Rieche, Marie; Landmann, Markus; Del Galdo, Giovanni (Proceedings of the 2013 IEEE-APS Topical Conference on Antennas and Propagation in Wireless Communications, IEEE APWC 2013, 2013)
Providing mobile users with communication services at all the times and places is the principal incentive for the development of SatCom On-The-Move (SOTM) applications. Fading due to objects surrounding the earth terminal and antenna de-pointing due to the vehicle motion represent the main challenges for the development of SOTM systems. In fact, both lead to degradation in the overall Quality of Service (QoS). Moreover, antenna de-pointing may lead to harmful interference to adjacent satellites. Regulatory authorities define limits for antenna de-pointing and for the Power Spectral Density (PSD) transmitted from the antenna. An integral part of the development of SOTM systems is to demonstrate their overall performance as well as to test the performance of the tracking unit. Such tests and demonstrations are usually performed in a field test where two or more operational satellites are involved. This contribution proposes a test methodology which avoids the employment of operational satellites and offers a reliable and repeatable environment for measuring the overall SOTM system performance. In particular, antenna pointing errors can be estimated with a high degree of precision. © 2013 IEEE.
CRIS-Team Scopus Importer:2025-11-10